Biochemical Investigation of Oil of Papaver somniferum - Khan, M.R.; Khawar, Z.; Latif, M. (Asian Journal of Chemistry, 2012)
The oil of Papaver somniferum was extracted with n-hexane and acetone. The oil was subsequently investigated for its fundamental properties and antibacterial activity. The residue of Papaver somniferum left after extraction was checked for antibacterial activity. It was observed that the oil extracted with n-hexane was not active against E. coli but was active against S. aureus, while the residue left after extraction was active against both pathogens. The oil extracted with acetone was active against E. coli but was inactive against S. aureus. Its residue was found active against E. coli but was inactive against S. aureus. The physical and chemical properties of oils were also determined and compared. The oils extracted were also subjected to thin layer chromatography to determine its polar and non-polar lipid components.